Indonesian Migrant Workers in Taiwan: The State Dilemma and People’s Realities - Ali Maksum; Ching-lung Tsay; Ali Muhammad (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2020)
The role of migrant workers is frequently marginalized amid industrial development, labor shortages, and the domination of state to state arrangements. In fact, the position of migrant workers should be considered as a primary factor in bilateral relations and trade agreements, notably between Indonesia and Taiwan. The reason is that the influx of migrant workers has undoubtedly given many benefits to both Indonesia and Taiwan governments. The Indonesian government considered that in the midst of insufficient job opportunities, migrant workers working in Taiwan indirectly lowered the unemployment rate. In addition, Indonesia acknowledged the high contribution of migrant workers by remittances to national income. At the same time, Taiwan recognized the importance of Indonesian migrant workers in the national economy, as well as strengthening Taiwan’s second-track diplomacy with Indonesia vis-à-vis China. This article argues the dynamics of Indonesian migrant workers in Taiwan, influenced by two factors: (1) the state dilemma and (2) people’s realities, affecting the international relations between Indonesia and Taiwan. Therefore, this paper aims to explore possible answers by discussing the state dilemma and peoples’ realities from the perspective of Indonesian workers in Taiwan. This study represents qualitative research supplemented by data obtained from interviews with Indonesian workers in Taiwan. The authors are also intensively contacted and involved through activities with Indonesian workers and communities.